The dual functional role of MicroRNA‐18a (miR‐18a) in cancer development. Issue 1 (23rd December 2019) - Shen, Kexin; Cao, Zhe; Zhu, Ruizhe; You, Lei; Zhang, Taiping
Abstract: The polycistronic miR‐17‐92 cluster is instrumental in physiological processes commonly dysregulated in cancer, such as proliferation, the cell cycle, apoptosis, and differentiation. MicroRNA‐18a (miR‐18a) is one of the most conserved and multifunctional miRNAs in the cluster and is frequently overexpressed in malignant tumors. Altered miR‐18a expression has been found in various physiological and pathological processes, including cell proliferation, apoptosis, epithelial–mesenchymal transition (EMT), tumorigenesis, cancer invasion and metastasis. In this review, we summarized the molecular basis and regulatory targets of miR‐18a in cancer development. Interestingly, miR‐18a has a dual functional role in either promoting or inhibiting oncogenesis in different human cancers. The differential miRNA expression in cancers of the same organ at different stages or of various subtypes suggests that this dual function of miR‐18a is independent of cancer type and may be attributed to the fundamental differences in tumorigenic mechanisms. Finally, we summarized the current clinical use of miR‐18a and discussed its potential uses in cancer therapy.